Pengaruh Karakteristik Sosial Demografi Terhadap Representasi Diri Generasi Z Pada Media Sosial Instagram Di Kota Bengkulu - Dhandy Thio Ramadhani S; Panji Suminar (STAI Bumi Silampari, 2025)
This study aims to analyze the influence of socio-demographic characteristics on self-representation among Generation Z on the social media platform Instagram in Bengkulu City. The socio-demographic characteristics examined include age, gender, and family background. The research employs a quantitative approach using a survey method involving 240 respondents from Generation Z residing in Bengkulu City, with an explanatory research design. Data were analyzed using Structural Equation Modeling (SEM) to examine the relationships between variables. The results indicate that socio-demographic characteristics including age, gender, and family background have a positive and significant influence on the self-representation of Generation Z on Instagram. These findings suggest that self-representation on social media is not a neutral act but is shaped by individuals’ social backgrounds, which influence how they construct and interpret their digital identities. This research provides theoretical contributions to the field of communication and new media studies, as well as practical implications for developing digital communication strategies tailored to the characteristics of younger generations. Furthermore, the study highlights the importance of understanding social dynamics in shaping patterns of interaction and self-representation in the digital era. For future research, it is recommended to expand the variables by incorporating psychosocial factors such as the need for validation, social anxiety, or perceptions of digital aesthetics. Future studies may also explore other social media platforms or generational groups to gain a broader understanding of self-representation dynamics in the digital culture context.